2013
DOI: 10.1136/bcr-2013-201621
|View full text |Cite
|
Sign up to set email alerts
|

Successful pregnancy in a woman with arthrogryposis multiplex congenita

Abstract: Arthrogryposis multiplex congenita refers to a clinical condition or syndrome characterised by multiple congenital contractures that affect two or more different areas of the body. Of the cases reported so far, an important percentage had to be terminated before pregnancy term, predominantly by caesarean section. We describe a 36 year-old woman who wanted to conceive. A multidisciplinary approach was set from the preconceptional period and special attention was given to respiratory function, potential anaesthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Other studies reported a lower number of married participants, which may be due to their sample being younger [ 36 , 37 , 39 ]. Support with family planning and obstetrical consultation are important to address concerns related to parenthood [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported a lower number of married participants, which may be due to their sample being younger [ 36 , 37 , 39 ]. Support with family planning and obstetrical consultation are important to address concerns related to parenthood [ 57 ].…”
Section: Discussionmentioning
confidence: 99%